exoALMA. XVI. Predicting Signatures of Large-scale Turbulence in Protoplanetary Disks - Marcelo Barraza-Alfaro; Mario Flock; William Béthune; Richard Teague; Jaehan Bae; Myriam Benisty; Gianni Cataldi; Pietro Curone; Ian Czekala; Stefano Facchini; Daniele Fasano; Misato Fukagawa; et al. (The Astrophysical Journal Letters)
Turbulent gas motions drive planet formation and protoplanetary disk evolution. However, empirical constraints on turbulence are scarce, halting our understanding of its nature. Resolving signatures of the large-scale perturbations driven by disk instabilities may reveal clues on the origin of turbulence in the outer regions of planet-forming disks. We aim to predict the observational signatures of such large-scale flows, as they would appear in high-resolution Atacama Large Millimeter/submillimeter Array observations of CO rotational lines, such as those conducted by the exoALMA Large Program. Post-processing 3D numerical simulations, we explored the observational signatures produced by three candidate (magneto)hydrodynamical instabilities to operate in the outer regions of protoplanetary disks: the vertical shear instability (VSI), the magnetorotational instability (MRI), and the gravitational instability (GI). We found that exoALMA-quality observations should capture signatures of the large-scale motions induced by these instabilities. Mainly, flows with ring, arc, and spiral morphologies are apparent in the residuals of synthetic velocity centroid maps. A qualitative comparison between our predictions and the perturbations recovered from exoALMA data suggests the presence of two laminar disks and a scarcity of ring- and arc-like VSI signatures within the sample. Spiral features produced by the MRI or the GI are still plausible in explaining observed disk perturbations. Supporting these scenarios requires further methodically comparing the predicted perturbations and the observed disks’ complex dynamic structure.